2022
DOI: 10.1177/2050313x221129782
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal reconstruction using a femoral head allograft and biologic adjuncts: A case report

Abstract: We present a case of calcaneal reconstruction after both an improvised explosive device injury and subsequent salvage procedures left the patient with a large calcaneal defect and damaged hindfoot soft tissue. A subtalar arthrodesis was performed with a femoral head allograft, where it was fused to the remaining calcaneus and superiorly through the talus, to successfully reconstruct this defect. Demineralized bone matrix, bone morphogenetic protein, and concentrated bone marrow aspirate were also added as adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The femur head allograft is a corticocancellous structural bone graft, and among the most used bone allografts. Its application in foot and ankle surgery has been reported mostly for arthrodesis procedures, whereas literature is sparse as regards its use for the reconstruction of calcaneal bone loss [12][13][14][15] . Loder et al and Weiss et al reported successful delayed calcaneal reconstructions with femur head allografts in two patients who developed post-traumatic osteomyelitis following ORIF treatment requiring calcaneal resections.…”
Section: Discussionmentioning
confidence: 99%
“…The femur head allograft is a corticocancellous structural bone graft, and among the most used bone allografts. Its application in foot and ankle surgery has been reported mostly for arthrodesis procedures, whereas literature is sparse as regards its use for the reconstruction of calcaneal bone loss [12][13][14][15] . Loder et al and Weiss et al reported successful delayed calcaneal reconstructions with femur head allografts in two patients who developed post-traumatic osteomyelitis following ORIF treatment requiring calcaneal resections.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients who have undergone complex traumatic injuries may develop demineralization, loss of bone mass, and decreased skeletal integrity, so-called post-traumatic osteoporosis (PTO) [1][2][3]. Advances in intensive care medicine have contributed to the increased survival of patients with previously terminal traumatic injuries, including those with polytraumas from high energy collision, burns, explosions, crush injuries, falls from height, and catastrophic events-increasing the incidence of this progressively debilitating pathology [4][5][6].…”
Section: Introductionmentioning
confidence: 99%